Characterization and genome analysis of Neobacillus mesonae NS-6, a ureolysis-driven strain inducing calcium carbonate precipitation - Xu, Rui; Zhang, Shuqi; Ma, Zhiwei; Rao, Qingyan; Ma, Yanling (Frontiers in Microbiology, 2023)
In this study, a highly promising bacterium was isolated from sandstone oil in the Ordos Basin, named strain NS-6 which exhibited exceptional urease production ability and demonstrated superior efficiency in inducing the deposition of calcium carbonate (CaCO3). Through morphological and physiochemical characteristics analysis, as well as 16S rRNA sequencing, strain NS-6 was identified as Neobacillus mesonae. The activity of urease and the formation of CaCO3 increased over time, reaching a maximum of 7.9 mmol/L/min and 184 mg (4.60 mg/mL) respectively at 32 h of incubation. Scanning Electron Microscopy (SEM) revealed CaCO3 crystals ranging in size from 5 to 6 m, and Energy Dispersive X-ray (EDX) analysis verified the presence of calcium, carbon, and oxygen within the crystals. X-ray Diffraction (XRD) analysis further confirmed the composition of these CaCO3 crystals as calcite and vaterite. Furthermore, the maximum deposition of CaCO3 by strain NS-6 was achieved using response surface methodology (RSM), amounting to 193.8 mg (4.845 mg/mL) when the concentration of calcium ions was 0.5 mmol/L supplemented with 0.9 mmol/L of urea at pH 8.0. Genome-wide analysis revealed that strain NS-6 possesses a chromosome of 5736360 base pairs, containing 5442 predicted genes, including 3966 predicted functional genes and 1476 functionally unknown genes. Genes like ureA, ureB, and ureC related to urea catabolism were identified by gene annotation, indicating that strain NS-6 is a typical urease-producing bacterium and possesses a serial of genes involved in metabolic pathways that mediated the deposition of CaCO3 at genetic level.